Not Everyone Is Engaged: An Innovative Approach to Measure Engagement Levels on the Labor Market - Carole Chartouni; Robert Holzmann; Gustavo N. Paez (Institute of Labor Economics (IZA), 2019)
Individuals' level of engagement on the labor market is hypothesized to be of critical importance for labor market outcomes. Based on a recent labor market survey in the Kingdom of Saudi Arabia (KSA), this paper develops an innovative index to measure individuals' labor market engagement across three dimensions: preferences, intensity, and barriers. The index can also to be used to cluster individuals with similar engagement levels to target labor market interventions more effectively and may be used to roughly measure the effectiveness of labor market interventions across time, as it can calculate the score for out-of-sample individuals. The index is computed individually and in aggregate for six labor market groups: employed, unemployed, and out-of-the-labor force, each separately for men and women. The methodology includes: (i) identifying labor subgroups and engagement dimensions, (ii) identifying relevant variables within each group and dimension, (iii) constructing an index for each group and dimension that captures the relative status of an individual against his/her reference group, and (iv) synthesizing the different engagement dimensions into a single indicator. Findings confirm the strong heterogeneity of labor market engagement in the KSA and the usefulness of differentiating interventions for job searchers depending on which cluster they belong to.
Keywords: C38; C43; J08; 330; intervention evaluation; index construction; labor market surveys; labor market programs; principal component method; profiling